Biological activity of extracts and hydrolysates from early- and adult-stage edible grasshopper Sphenarium purpurascens - Marín-Morales, M. Selene; Ibarra-Herrera, Celeste C.; Luna-Vital, Diego A.; Monribot-Villanueva, Juan L.; Guerrero-Analco, José A. (Frontiers in Nutrition, 2022)
Edible insects have become a promising food source because they are rich in protein, fatty acids, minerals, among others. In recent years, edible insects have been proposed to be used as innovative functional ingredients in terms of biological activity. The present study aimed to determine and compare biological activities of the extracts and hydrolysates obtained from early- and adult-stage edible grasshoppers Sphenarium purpurascens to evaluate their potential as source of bioactive compounds. Proximal analyses showed that in adult grasshoppers, the percentage of protein (48.9%±1.2), crude fat (13.1%±0.09), and chitin (15.6%±0.81) were significantly higher than early grasshoppers (42.2%±0.55, 9.35%±0.08 and 10.5%±0.15 respectively). Total phenolic compounds, DPPH•, and ABTS•+ free radical scavenging were analyzed and reported. Enzymatic hydrolysis increased the concentration of total phenolic compounds and higher antioxidant capacity (up to 252.78 mM Trolox). Once fractionated by ultrafiltration the fraction that presented the highest antioxidant activity against DPPH• and ABTS•+ was that with molecules ≤10 kDa. Furthermore, the bioaccessibility of the samples was analyzed by in vitro protein digestion with the multi-enzymatic method and a recovery index was reported. Extracts and hydrolysates were analyzed with HPLC-MS, and this allowed the identification of phenolic acids and flavonoids. The results obtained in this work suggest that the grasshopper can be used as a possible source of bioactive compounds that can be used in food or pharmaceutical industry.